Urothelial carcinoma in the ureteral stump of a nefrectomized patient by kidney exclusion: a case report - Campos, Tadeu J. F. L.; Leandro, Plinio H. F.; Lima, Lucas de O.; Lima, André C. M.; Aquino, Lucas de A.; Rocha, Marcos F. H. (International Surgery Journal, 2021)
Urothelial carcinoma of the upper urinary tract is a rare and potentially aggressive disease. It rarely affects the ureter and is quite uncommon in the ureteral stump of a patient who has already undergone nephrectomy for benign disease. We, herein, describe a case of a male patient who underwent total left nephrectomy owning to renal exclusion. After three years, owning to an episode of hematuria, he was diagnosed with a urothelial tumor of the ureteral stump, and he underwent ureterectomy and excision of the bladder cuff. The involvement of the ureteral stump by urothelial tumor is an extremely rare event and is normally associated with poor prognosis owning to the delay in diagnosis inherent to atypical presentation. The most common symptom is hematuria. Pain is uncommon because of the absence of a renal unit and consequently, hydronephrosis. Although rare, we must remember the possibility of the appearance of primary tumors in the ureteral stump and maintain a high degree of diagnostic suspicion to avoid diagnosis in advanced stages.